SARM1 Promotes Photoreceptor Degeneration in an Oxidative Stress Model of Retinal Degeneration - Gibbons, Luke; Ozaki, Ema; Greene, Chris; Trappe, Anne; Carty, Michael; Coppinger, Judith A.; Bowie, Andrew G.; Campbell, Matthew; Doyle, Sarah L. (Frontiers in Neuroscience, 2022)
SARM1 (sterile alpha and armadillo motif-containing protein) is a highly conserved Toll/IL-1 Receptor (TIR) adaptor with important roles in mediating immune responses. Studies in the brain have shown that SARM1 plays a role in induction of neuronal axon degeneration in response to a variety of injuries. We recently demonstrated that SARM1 is pro-degenerative in a genetic model of inherited retinopathy. This current study aimed to characterise the effect of SARM1 deletion in an alternative model of retinal degeneration (RD) in which the retinal pigment epithelium (RPE) fragments following administration of oxidising agent, sodium iodate (NaIO3), leading to subsequent photoreceptor cell death. Following administration of NaIO3, we observed no apparent difference in rate of loss of RPE integrity in SARM1 deficient mice compared to WT counterparts. However, despite no differences in RPE degeneration, photoreceptor cell number and retinal thickness were increased in Sarm1-/- mice compared to WT counterparts. This apparent protection of the photoreceptors in SARM1 deficient mice is supported by an observed decrease in pro-apoptotic caspase-3 in the photoreceptor layer of Sarm1-/- mice compared to WT. Together these data indicate a pro-degenerative role for SARM1 in the photoreceptors, but not in the RPE, in an oxidative stress induced model of retinal degeneration consistent with its known degenerative role in neurons in a range of neurodegenerative settings.